Strategic Management of Tahfidz Curriculum for Early Childhood: Comparative Perspectives of Al-Khabisi and Ibn Khaldun - Muhamad Wijaksono; Lalu Turjiman Ahmad; Iwan Falahudin; Aas Siti Sholichah (Al-Qalam Institue, 2026)
This study aims to analyze the Qur’an memorization (tahfidz) curriculum for early childhood from the perspectives of Al-Khabisi and Ibn Khaldun and examine its implications for contemporary Islamic educational management. This research employed a qualitative library research design using philosophical and comparative approaches. Data were collected from classical and contemporary literature, including books, journal articles, and educational documents, and analyzed through descriptive qualitative content analysis involving data reduction, presentation, and conclusion drawing. The findings indicate that Al-Khabisi emphasized intensive Qur’an memorization during early childhood as a strategic stage for strengthening memory and shaping Islamic character, while Ibn Khaldun promoted a gradual, psychologically adaptive, and child-centered learning process integrating memorization with understanding. Both scholars agreed that the Qur’an should serve as the primary foundation of early childhood Islamic education and character formation. The study implies that contemporary tahfidz curriculum management should combine structured memorization, discipline, and habituation with developmentally appropriate and humanistic approaches to support children’s spiritual, intellectual, emotional, and moral development.